THE CLASH BETWEEN RELIGION, MEDICINE AND LOCAL BELIEFS IN THE SUN TRADITION IN LILINTA VILLAGE, RAJA AMPAT REGENCY - Khoirunnisa, Ulfa; Nawir, M. Syukri; Zulihi, Zulihi; Rian Efendi (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
This study aims to describe the 'Sun' (Pamali) Tradition in the Lilinta Community and see the 'Sun' (Pamali) Tradition in Lilinta Village from an Islamic point of view and see the 'Sun' Tradition from a medical point of view. The research location is in Lilinta Village, West Misool District, Raja Ampat Regency. Data were obtained from primary data sources, namely a collection of stories from the community about sun or pamali in Lilinta Village through interviews. The data collection technique used is to go directly to the field to observe and record activities carried out by the community, especially those related to the 'Sun' tradition. The research uses semi-structured interviews, which focus on prepared questions. The results show that the existence of the 'Sun' tradition is to respect the behavior of these animals towards their ancestors. However, regarding the impact that is obtained if violating the 'Sun' from the point of view of Islam and the medical point of view, they are contradictory or have nothing to do with it.